Infrastuktur Teknologi Informasi yang Menunjang Strategi Bisnis pada Perusahaan Tambang: Studi Kasus PT XYZ - Suryani, Eli (Bina Nusantara University, 2013)
The purposeof this study is to analyze, evaluate and recommend infrastructure of information technology that addresses its flexibility to run along the continouing development of the company, to avoid the potential risk that may come which is more costly for the company due to failure in dealing with those changes.To obtain more accurate data and information, this study uses observation and interview technique with the top management and key person from Information Technology Department. It can be concluded that strengthening the information technology infrastructure is able to strengthen business processes that built upon it, and enhance more value to the company.